2019
DOI: 10.1002/bbb.2046
|View full text |Cite
|
Sign up to set email alerts
|

Herbicides based on pelargonic acid: Herbicides of the bioeconomy

Abstract: Following the first generation of natural herbicide products based on pelargonic acid as an active ingredient, a number of new herbicides and blossom thinners based on C9:0 saturated fatty acid entered the marketplace in many countries, offering a long-awaited safer alternative to synthetic chemical herbicides. This study addresses key production and bioeconomy aspects prior to the expected widespread adoption of n-nonanoic acid as an alternative ingredient of new biobased herbicides, derived from the fatty ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 21 publications
1
47
0
Order By: Relevance
“…The performance of PA herbicides depends on the concentration used and requires maximum coverage of the treated plant organs 17,20 . Climate conditions also interfere substantially their phytotoxic activity 15–17 . Thus, to prcevent external factors from affecting the efficacy of the test preparations, prior trials on climate conditions, weed size and application rate were performed (data not shown).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The performance of PA herbicides depends on the concentration used and requires maximum coverage of the treated plant organs 17,20 . Climate conditions also interfere substantially their phytotoxic activity 15–17 . Thus, to prcevent external factors from affecting the efficacy of the test preparations, prior trials on climate conditions, weed size and application rate were performed (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, some of the most popular products for sustainable weed control are fatty acids (FA) with a carboxylic chain length of between eight and ten carbons, for example pelargonic (nonanoic) acid (PA) or a mixture of caprylic and capric acids 12,15–17 . For many years, the rancid odour of short‐chain FA has restricted its use in gardens, industry or crop production greenhouses, despite its popularity as a natural herbicide 15,18 . Currently, PA is the main proposed alternative for natural weed control in agriculture, being the most studied FA herbicide 15–18 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comprehensive reviews are available covering the use of essential oils as herbicidal substances [ 51 ], along with other natural active ingredients [ 60 ]. The results of this study show that the water extract of A. alba needles produced via hydrodynamic cavitation has an inhibitory effect on the germination of most weed species, in comparison to the control.…”
Section: Discussionmentioning
confidence: 99%
“…Worthy of note is the fact that the commercial process for the synthesis of AA is accompanied by the formation of pelargonic acid (nonanoic acid, PA), which is characterized by a good antimicrobial activity and is used as sanitizing agent for food and in personal care products, as well as in the production of herbicides. [10] Even more it is employed as a precursor of solvent for varnishes. [11] There are currently two main industrial technologies for the synthesis of these platform molecules:…”
Section: Introductionmentioning
confidence: 99%